Skill development in Indian agriculture and food processing sectors: A scoping exercise - Kavery Ganguly; Ashok Gulati; Joachim von Braun (University of Bonn, Center for Development Research (ZEF), 2019)
The agriculture and food sector in India employ a significant proportion (about 44 percent) of the workforce, the majority of whom are not very educated and lack formal or informal skill training. Hence, they are unable to make the most out of their occupation. About 67 percent of the population in India is aged 15-64 years while 27 percent is aged 0-14 years (UNFPA n.d.). This offers both a challenge and an opportunity to skill the youth as well as the existing workforce in India with the objective to improve their productivity and enhance their incomes. This paper is a scoping study of policies and institutions that are operational in this context of skill formation in India, with a focus on the agriculture and food sector. It takes stock of ongoing initiatives and programs, their design and scope in achieving skill development in general and related to the agriculture and food sector in particular. In terms of policy, skill development has been accorded high priority with an objective to make the programs aspirational for youth as well as for them to recognize the value of experience and knowledge. The focus is laid on quality of training, assessment, and certification thus ensuring standards and greater market acceptability. These are prerequisites for investments in skills to bring higher returns in terms of remunerative jobs. The government has been a catalyst of change in this area in terms of designing, implementing and financing of such programs. The role of private players including both potential employers as well as global partners (government, business and nongovernmental organizations) has been widely recognized in upgrading the scope, target and outcomes as well as ensuring sustainability of the national skill development program. As technology plays a very important role in sustainable value chains, it creates demand for a better skilled workforce, and accordingly rewards them with better paid jobs and higher returns in farming. Hence designing appropriate qualification packs and training programs with a focus on innovations all along the value chains (that help promote technology adoption, facilitate effective value chain management, etc.) are critical. Also, innovative models of outreach (for example, classroom training for agricultural professionals, agricultural entrepreneurs, farmer field schools, and e-platforms) can add substantial value to skills at very low cost. Hence, scaling up fast is necessary to benefit the agriculture and food sector in India. While this paper gives an overview of the landscape of various programs and projects, and how they are being implemented by various actors (government, domestic private sector and international agencies), there is dire need to evaluate their outcomes in terms of increased incomes and more stable jobs of those trained through these programs.
Keywords: J21; J24; J43; Q16; 330; skill development; vocational training; agriculture and food